Evaluation of Short Term Complications of Inguinal Lymph Node Dissection for Skin and Urogenital Cancer (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Therapeutic lymphadenectomy is the standard treatment for patients with node positive malignant melanoma, squamous cell carcinoma (SCC) of penis, vulva and lower extremity skin. It has been shown to improve outcomes in some patients. However, inguinal lymph node dissection (ILND) has been associated with significant postoperative morbidity.Methods: This prospective observational study was conducted in the Departments of Surgical Oncology, Plastic &Reconstructive Surgical Oncology and Uro-Oncology of NICRH, Dhaka for a period of twelve months. A total of 41 patients with skin and urogenital malignancy involving inguinal lymph node undergoing inguinal lymph node dissection were included after getting informed written consent. Socio-demographic profile, cancer status and other related information were collected by preformed questionnaire. All data were analyzed by IBM SPSS v25.Result: Among all, 58.5% of the patients were aged between 40 to 60 years with male predominance (53.7%). Preoperatively, 78% of the patients had malignant melanoma and 22% of the patients had squamous cell carcinoma. Wound infection (31.7%) was most common complications followed by 22% of the patients had developed wound dehiscence, 22% had developed seroma, 12.2% had flap necrosis, 4.9% had hematoma, 4.9% had lymphadenoma and 2.4% showed graft failure. Older age and cancer status had impact on post-operative outcome but no significant association found (